COMPARATIVE EFFICACY OF FOLIAR FEEDING VERSUS SOIL APPLICATION OF BORON AND ZINC FERTILIZERS FOR ECONOMIC SEED COTTON PRODUCTION - Shabab-ud-Din; Ahmad, Fiaz; Akhtar, Muhammad Naeem; Murtaza, hulam (Journal of Research (Science), 2008)
Studies were carried out in Soltanpur series (Typic Ustochrepts) to quantify the effects of boron and zinc fertilizers, applied through soil and foliar methods on fruit production, seed cotton yield and economic analysis. The trial was laid out at Central Cotton Research Institute, Multan during the year 2005-2007. The treatments consisted of soil application with three levels each of boron (B) [0, 2.5, 5.0 kg B ha-1] and zinc (Zn) [0, 5, 10 kg Zn ha-1] in comparison to foliar feeding with three levels each of B (0, 1.25, 2.5 kg B ha-1) and Zn (0, 2.5, 5.0 kg Zn ha-1). The design of the experiment was randomized complete block with three replications. In soil application, the whole quantity of B and Zn was applied at the time of planting. In foliar application method, the whole quantity was split into five equal does and applied at day 30, 45, 60, 75 and 90 after planting. Cotton cv. CIM-496 was used as test crop. The basal dose of nitrogen, phosphorus and potassium was 150 kg N, 50 kg P2 O5 and 50 kg K2O ha-1. The results revealed that fruit production per unit area increased whereas fruit shedding percentage decreased at all levels of B and Zn fertilization, irrespective of application methods. Seed cotton yield increased by 11%, boll number by 19%, boll weight by 4.3% and chlorophyll SPAD values by 16%, over control, irrespective of application method. Foliar application of B and Zn proved to be superior by producing, on an average, 4.5% higher seed cotton yield than the soil application method. The economic analysis revealed that foliar application, on an average, produced VCR value of 7.15:1 with a net profit of Rs. 8492/- as compared to 2.25:1 and net profit of Rs. 3437/- in soil application method.